ChemInform Abstract: A New Approach for the Synthesis of N‐Sulfonyl Hydantoins. Issue 48 (2nd December 2014) - Rmedi, Hamdi; Baklouti, Ahmed
Abstract The triethylamine mediated reaction of α‐bromoacetamides with N‐sulfonyl isocyanates gives urea salts which undergo intramolecular cyclization to N‐sulfonyl hydantoins under thermal conditions.